# Multiply.Use the distrutive property: -0.3x(-1.2x-0.3x+0.50) Hint:x(x^2)=x(x)(x)=x^3

*print*Print*list*Cite

-0.3x(-1.2x - 0.3x + 0.50)

The distributive property means you must "distribute" the -0.3x in front of the brackets by multiplying it by each term in the bracket.Thus:

= (-1.2x)(-0.3x) - (0.3x)(-0.3x) + (0.50)(-0.3x)

= `(0.36x^2) - (- 0.09x^2) + (-0.15x)`

Note how some of the symbols have changed when we multiply by a negative (-). Now simplify those negatives and remove brackets:

= `0.36x^2 + 0.09x^2 - 0.15x`

We have "like terms" so can add them together.

= **0.45x^2 - 0.15x**

-0.3x(-1.2x-0.3x+0.50) you have to multiply each number on the inside of the parenthesis by the number on the outside which is -0.3x

`-0.3x xx-1.2x= .36x^2 `

`-03.x xx -0.3x = .09x^2 `

`-0.3x xx .50= -.15x `

`.36x^2+.09^2-.15x `

combine the like terms

`(.36x^2+.09^2)-.15x `

`.45^2-.15x` and that;s the answer